2018
DOI: 10.7759/cureus.2851
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Completeness and Timeliness of National Malaria Surveillance System in Qatar, 2016

Abstract: BackgroundThe high influx of migrant workers from malaria-endemic countries along with the presence of a malaria vector in Qatar has raised the alarm of the possible reintroduction of local transmission. Meanwhile, the Qatar Malaria Surveillance System aims to detect any local malaria transmission as well as to monitor trends in imported cases.AimEvaluating the attributes of the Malaria Surveillance System in Qatar will help identify any gaps necessitating rectification.MethodThe completeness and timeliness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
3
6
0
Order By: Relevance
“…In most cases the notification delay was divided into components with descriptive statistics provided for each component. Similar pattern was observed in more recent studies as well [ 14 18 ]. Instead of reporting the proportion of cases that meet and/or does not meet a specific time frame, we rather report the impact of notification delay on the parameters that define the occurrence of the disease.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In most cases the notification delay was divided into components with descriptive statistics provided for each component. Similar pattern was observed in more recent studies as well [ 14 18 ]. Instead of reporting the proportion of cases that meet and/or does not meet a specific time frame, we rather report the impact of notification delay on the parameters that define the occurrence of the disease.…”
Section: Discussionsupporting
confidence: 92%
“…We apply epidemiological soundness criteria in combination with the Latent Influence Point Process (LIPP) [ 10 ] and time-to-event [ 11 ] models to estimate these relations by utilizing the disease occurrence, meteorological and human population mobility data. Unlike prior studies where the timeliness of the disease surveillance is measured by comparing the average notification delay and its components to predefined, standardized and/or disease specific timeframes [ 12 18 ], our methodology quantifies the timeliness by measuring the case fertility (whether a case leads to secondary cases) and reproduction (number of secondary cases per fertile case) as well as the outbreak size and generations (of the infection chain). While the traditional approach is important to identify the overall performance gaps, our approach goes a step further by measuring the impact of these gaps on the occurrence of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The penjawi or pustu collects data every week at the health centers. Every Similar results in a study in the Solomon Islands found that lack of training and refresher [16][17][18] , high workload and lack of professional staff could lead to reporting delays 19 . Research in Uganda found an increase in the achievement of indicators for completeness of reports by training malaria officers 20 .…”
Section: Processsupporting
confidence: 60%
“…The findings are similar to the completeness in Sierra Leone 91%, Ghana 96%, 25 , 28 contrary to the Qatar study, 47%. 29 Bear in mind that the completeness in the previous studies is for 1 disease, for example, malaria surveillance in Qatar, not overall system completeness. According to the benchmark standard target of performance of developing countries is 80% based on WHO and CDC guide for Africa( 30 ) the timeliness of reporting communicable diseases was under a standard (68.9%) in 2020 in the Kurdistan region, whereas completeness was reasonably high.…”
Section: Discussionmentioning
confidence: 99%